TEACHING SYSTEMATIC THEOLOGY IN THE SOUTHERN AFRICAN CONTEXT: A SURVEY OF CURRENT PRACTICES - Conradie, Ernst M. (Scriptura, 2005)
This survey is based on data which I collected through colleagues at various theological institutions in the Southern African region.1 These institutions count amongst the most prominent theological institutions in the region. The data therefore provides a fairly reliable picture of how Systematic Theology is being taught at an undergraduate level at universities in the region.